2014
DOI: 10.2147/cia.s54978
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions conducted in clinical or community settings to improve dual-task postural control in older adults

Abstract: BackgroundInjury due to falls is a major problem among older adults. Decrements in dual-task postural control performance (simultaneously performing two tasks, at least one of which requires postural control) have been associated with an increased risk of falling. Evidence-based interventions that can be used in clinical or community settings to improve dual-task postural control may help to reduce this risk.PurposeThe aims of this systematic review are: 1) to identify clinical or community-based interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
115
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 62 publications
2
115
0
7
Order By: Relevance
“…Indeed, previous studies (Friedman et al, 2002;Mendes da Costa et al, 2012;Murphy et al, 2002) have reported that restriction in ADL affects about 46%-56% older adults with FOF, underlining the necessity of intervention programmes focused on decreasing FOF and increasing ADL ability. Physical intervention programmes may decrease the FOF (Brustio, Magistro, Ivaldi, Caglio, Rabaglietti, & Liubicich, 2015;Huang, Chung, Chen, Chin, & Wang, 2016;Sjosten, Vaapio, & Kivela, 2008;Zijlstra et al, 2005) and decrease the DTC (Agmon, Belza, Nguyen, Logsdon, & Kelly, 2014); thus, we hypothesised, based on our results, that interventions focused on decreasing FOF (e.g. physical or cognitive interventions) and DTC may have positive effects by maintaining or improving ADL functionality, which is linked with successful ageing.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, previous studies (Friedman et al, 2002;Mendes da Costa et al, 2012;Murphy et al, 2002) have reported that restriction in ADL affects about 46%-56% older adults with FOF, underlining the necessity of intervention programmes focused on decreasing FOF and increasing ADL ability. Physical intervention programmes may decrease the FOF (Brustio, Magistro, Ivaldi, Caglio, Rabaglietti, & Liubicich, 2015;Huang, Chung, Chen, Chin, & Wang, 2016;Sjosten, Vaapio, & Kivela, 2008;Zijlstra et al, 2005) and decrease the DTC (Agmon, Belza, Nguyen, Logsdon, & Kelly, 2014); thus, we hypothesised, based on our results, that interventions focused on decreasing FOF (e.g. physical or cognitive interventions) and DTC may have positive effects by maintaining or improving ADL functionality, which is linked with successful ageing.…”
Section: Discussionmentioning
confidence: 90%
“…The fact that the gains in postural control were more pronounced in dual-task conditions is particularly interesting, since dual balance task are ecologically more valid, and may have an added value over the single balance task for fall prediction (Bergland & Wyller, 2004;Verghese et al, 2002). Also, recent research synthesis indicates that dual-task training appears to be necessary to improve dualtask performance (Agmon, Belza, Nguyen, Logsdon, & Kelly, 2014). The applied Huber intervention was a dual-task since the subjects were required to precisely modulate force applied on the handles via hitting the target area on the screen (see Section 2).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of dual-task interference in older adults is evidenced by the growing number of systematic reviews addressing the topic [1,[6][7][8][9][10][11][12][13][14][15] , with 5 of these focusing specifically on treatment effects for dual-task gait and mobility [7-9, 13, 14] . The earliest of these reviews [9] examined the effects of cognitive and cognitive-motor interventions on physical functioning in older adults and adults with stroke or traumatic brain injury; however, the authors did not explicitly examine intervention effects on dual-task walking or dual-task interference.…”
Section: Introductionmentioning
confidence: 99%